2020
DOI: 10.1002/cne.24973
|View full text |Cite
|
Sign up to set email alerts
|

Light adaptation mechanisms in the eye of the fiddler crab Afruca tangeri

Abstract: A great diversity of adaptations is found among animals with compound eyes and even closely related taxa can show variation in their light-adaptation strategies. A prime example of a visual system evolved to function in specific light environments is the fiddler crab, used widely as a model to research aspects of crustacean vision and neural pathways. However, questions remain regarding how their eyes respond to the changes in brightness spanning many orders of magnitude, associated with their habitat and ecol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 69 publications
1
32
0
Order By: Relevance
“…The auto-segmentation method not only extracts the elongation axis of the crystalline cones but also their full shape. This is interesting because several arthropod species modify the length (Brodrick et al, 2020; Menzi, 1987; Nilsson and Odselius, 1981) and the diameter (Brodrick et al, 2020) of their crystalline cones in response to changes in light levels. In fiddler crabs, these light-adaptation mechanisms together with modifications of the rhabdoms enhance optical sensitivity at night (Brodrick et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The auto-segmentation method not only extracts the elongation axis of the crystalline cones but also their full shape. This is interesting because several arthropod species modify the length (Brodrick et al, 2020; Menzi, 1987; Nilsson and Odselius, 1981) and the diameter (Brodrick et al, 2020) of their crystalline cones in response to changes in light levels. In fiddler crabs, these light-adaptation mechanisms together with modifications of the rhabdoms enhance optical sensitivity at night (Brodrick et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This is interesting because several arthropod species modify the length (Brodrick et al, 2020; Menzi, 1987; Nilsson and Odselius, 1981) and the diameter (Brodrick et al, 2020) of their crystalline cones in response to changes in light levels. In fiddler crabs, these light-adaptation mechanisms together with modifications of the rhabdoms enhance optical sensitivity at night (Brodrick et al, 2020). The auto-segmentation method generates opportunities for large scale investigation of these light-adaptation properties at numerous light levels and across large numbers of species.…”
Section: Resultsmentioning
confidence: 99%
“…In this study we focused on the migration of screening pigments that has been shown to occur in L. pugilator (Fielder et al, 1971;Fingerman, 1970;Reddy et al, 1997) and differential regulation of opsin gene expression (DeLeo and Bracken-Grissom, 2020;Katti et al, 2010). Although there is no evidence that the latter occurs in fiddler crabs, there is evidence to suggest that the rhabdom width of the fiddler crab A. tangeri does fluctuate diurnally (Brodrick et al, 2020). The possibility of a shift in spectral sensitivity due to A1 to A2 chromophore lability was not modelled in our study as no brachyuran crab has been shown to utilise A2-based porphyropsin visual pigments (Cronin and Forward, 1988).…”
Section: Diurnal Shifts In Spectral Sensitivitymentioning
confidence: 99%
“…Increases in rhabdom length would be predicted to broaden spectral sensitivities (Brindley, 1960), but it is possible for changes in rhabdom width to alter spectral sensitivity too. Diurnal changes in rhabdomeric width have recently been shown for the fiddler crab A. tangeri (Brodrick et al, 2020). If waveguide modes vary as a result, it is possible that the contribution of surrounding screening pigments to spectral rhabdomeric absorption could affect the cells' overall spectral sensitivity, with smaller diameter cells predicted to be more affected than larger ones (Van Hateren, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…MicroCT (μCT), a 3D X-Ray imaging technique burgeoning in use among comparative morphologists (Baird and Taylor 2017; Buser et al 2020), is a rich and valuable resource to study arthropod vision. It has been used on arthropods to study muscles (Walker et al 2014), brains (Smith et al 2016), ocelli (Taylor et al 2016), and eyes (Brodrick et al 2020; Gaspar et al 2019; Taylor et al 2018, 2020). Visualizing internal structures in 3D allows calculating visual parameters for non-spherical compound eyes, measuring anatomical IO angles at very high spatial resolution, and segmenting different tissues, such as visual neuropils, within the same dataset.…”
mentioning
confidence: 99%